Bibliographies. (Bulletin of the Institute of Classical Studies, 2022)
187 Kouloumentas, S. 2018: 'Prodicus on the rise of civilization: religion, agriculture and culture heroes', Philosophie Antique 18, 127-52. 188 Landi, A. 2012: "Forme e strutture del culto di Gaia nel mondo Greco", Archeologica Classica 63, 127-67. 189 Lebedev, A. V. 1989: "Heraclitus in P. Derveni", Zeitschrift für Papyrologie und Epigraphik 79, 39-47. 190 - - 2020: 'Democritus on Iranian magi and ancient religion: a quotation from Avesta (Yt.1,7) in Democritus fr.580 Luria', Indo-European Linguistics and Classical Philology 24, 129-50. 191 Ledger, G. 1989: Re-counting Plato: A Computer Analysis of Plato's Style, Oxford. 8 - - 2015: "Gods: Olympian or Chthonian", in E. Eidinow and J. Kindt (eds), The Oxford Handbook of Ancient Greek Religion, Oxford, 355-68. 9 Detienne, M., and J. P. Vernant 1978: Cunning Intelligence in Greek Culture and Society, trans. 40 Andersen, M. 2019: "Predictive coding in agency detection", Religion, Brain & Behavior 9, 1-20. 41 Arthur, S. 2018: 'Wafting incense and heavenly foods: the importance of smell in Chinese religion', Body and Religion 2, 144-66. 42 Barrett, J. L. 2004: Why Would Anyone Believe in God? Google Scholar Google Preview OpenURL Placeholder Text WorldCat COPAC 10 Eidinow, E. 2011: 'Networks, negotiation, and narrative: a model for ancient Greek religion', Kernos 24, 9-38. 11 - - 2015: "Ancient Greek religion: "embedded" ... and embodied", in C. Taylor and K. Vlassopoulos (eds), Communities and Networks in the Ancient Greek World, Oxford, 54-79. 12 - - 2018: 'Serapis at Alexandria: the creation and "destruction" of religious networks', in M. Dana and I. Savalli-Lestrade (eds), La cité interconnectée: transferts et réseaux institutionnels, religieux et culturels aux époques hellénistique et impériale, Paris, 183-204.